Ambivalence: The Divided Self in Sylvia Plath's Poetry - Sharif, Mohd Yasin (IIUC Studies, 2009)
Ambivalence, mixed good and bad feelings about particular entity, individual or circumstance, became a ruling passion in Sylvia Plath's life. These ambivalence and breakdown are closely dealt with in her poems. Confessional poets usually reveal their own personal experiences without straining excruciating sentiment. Sylvia Plath, one of the 1960s most influential confessional poets used the same resentment and anguish that developed from her personal grief as the subject of many of her poems. SP is well known among the celebrities for her ambivalence schizophrenic, schizoid and paranoid nature. As an obsessive-compulsive neurotic, ambivalence dominated both her works as well as her life. This ambivalent personality of SP made her and her works obscure and bizarre to the readers. Many of her poems bear the evidence of narcissism, self-hatred, deep attachment and simultaneously deep hatred towards her dear and near ones. The present study is an endeavor to interpret this complex ambivalent personality of SP in light of her poems, her journals and her letters where she clearly confesses all her neurotic obsessed activities directly, honestly and sincerely without any hesitation. The study will also dug out the true logical reasons that lead to the suicide of a blooming star in her make up. doi: 10.3329/iiucs.v3i0.2628 IIUC STUDIES Vol. - 3, December 2006 (p 7-18)